Formulasi Dan Pengujian Sediaan Deodorant Spray Yang Mengandung Ekstrak Daun Kemangi (Ocimum Basilicum L.) Terhadap Bakteri Staphylococcus Aureus - Devina Chandra; Manuppak Irianto Tampubolon; Natanael Priltius (PPNI UNIMMAN, 2023)
Basil leaves are very rich in nutritious substances. Among them are beta carotene, vitamin C, macro minerals (calcium, phosphorus, magnesium). This plant is included in the Lamiaceae family which contains various chemical compounds, including phenols, saponins, alkaloids, flavonoids, tannins, and essential oils. The benefits of basil have been widely applied in people's lives as traditional medicine, for example, basil leaves are used to treat, cough, colds and so on. Body odor can be caused by several factors such as genetic factors, psychological conditions, food factors, obesity factors and clothing materials used.One of the triggers of body odor due to bacterial infection, namely Staphyloccous aureus bacteria.This study aims to formulate deodorant spray ethanol extract of basil leaves, test the physical properties of deodorant spray preparations, and determine whether the preparation of deodorant spray ethanol extract of basil leaves can inhibit staphylococcus aureus bacteria. Physical tests were carried out on days 0 (after manufacture) and 7 with the results of the organoleptical physical test of the preparation having a distinctive odor of basil, brownish yellow in color, It has a pH of 4 which corresponds to the pH of the skin, and experiencing an increase in viscosity on day 7 examination. The antibacterial test results of formulations 1, 2, and 3 showed inhibition of the banteri.